Ornithine Transcarbamylase Deficiency Presenting as Acute Liver Failure in Girls: A Paediatric Case Series. Issue 2 (August 2020) - Selvanathan, Arthavan; Hertzog, Ashley; Lemberg, Daniel A.; Ellaway, Carolyn
Abstract : ABSTRACT: Ornithine transcarbamylase deficiency (OTCD) is the most common of the urea cycle disorders and follows an X-linked inheritance pattern. The classical form in male infants causes vomiting and lethargy in the neonatal period; if untreated the severe hyperammonaemia can cause acute neurotoxic complications and permanent disability. OTCD may also occur in heterozygote female individuals, though the manifestations are variable. We report 2 cases of female paediatric patients with OTCD, who presented with acute liver failure. Both patients had limited oral intake at the time of presentation, causing an absence of orotic aciduria, which delayed the diagnosis. These cases demonstrate the need to consider urea cycle disorders in children presenting with acute liver failure, and that repeating the urine metabolic screen at the time of an unrestricted diet is warranted if there is a high clinical suspicion. Abstract : Supplemental Digital Content is available in the text